MANAGEMEN FISIOTERAPI DENGAN TERAPI LATIHAN PADA KASUS LOW BACK PAIN ET. CAUSA ISCHIALGIA: A CASE REPORT - Lusia Intan Purnamasari; Umi Budi Rahayu; Kingkinnarti Kingkinnarti (Journal of Innovation Research and Knowledge, 2023)
Background: Ischialgia is a manifestation of low back pain that occurs due to clamping of the ischiadicus nerve which causes paraesthesia/tingling along the course of the ischiadicus nerve roots, this condition will cause low back pain. Complaints are felt such as discomfort, limited movement that interferes with functional activities. Exercise therapy is given an effect in repairing, recovering, and increasing the body's physiology and physical function. The types of exercise therapy given are stretching, core stability and strengthening. Objektive: Knowing physiotherapy management with exercise therapy methods in case of low back pain et. causa ischialgia. Methods: Research using the Case Report method was carried out at Dr. Harjono S Ponorogo Hospital in a 66-year-old male patient diagnosed with physiotherapy for low back pain et. causa ischialgia with complaints of lower back pain and feeling pain radiating to the right hind thigh. Patients were given intervention in the form of exercise therapy which was carried out 1 week 2 times. Result: The exercise therapy which was carried out 3 times resulted in a decrease in pain, an increase in muscle strength, an increase in trunk LGS, there was no increase in functional activity, and there was an increase in measurements of the risk of falling. Conclusion: Based on the research using Case Report, it shows that physiotherapy management with the exercise therapy method in cases of low back pain et. causa ischialgia, as a whole the evaluation results found an increase.